The Catholic Church and the Dutch Bible : from the Council of Trent to the Jansenist controversy (1564-1733) - Agten, Els, 1985- (Brill's series in church history and religious culture, 2020)
"In The Catholic Church and the Bible: From the Council of Trent to the Jansenist Controversy (1564-1733), Els Agten studies the impact of Jansenism and anti-Jansenism on the ideas regarding vernacular Bible reading and Bible production in the Low Countries in the broader seventeenth century. The book provides a review of sixteenth- and seventeenth-century book censorship and an analysis of the ideas and the writings of ten protagonists, including theologians, Bible translators, ecclesiastical authorities and representatives of Port-Royal. This way, Agten demonstrates that the Jansenists were stimulating the laity, with the inclusion of women and children, to read the Bible in the vernacular, with no restrictions whatsoever. Their opponents, in contrast, adopted a more wary position"--